Model of religious character education: A case study in Al-Hilal Islamic Primary School Bekasi, Indonesia - M Husnaini; Irnie Victorynie; Noor Amili (Journal of Social Studies (JSS), 2020)
Presidential Regulation Number 87 of 2017 Article 2 states that character education must be the leading spirit in Indonesia's delivery of education. This study aims to describe the religious character education model implemented at Al-Hilal Islamic Primary School Bekasi, which is supported by students' parents' participation to build a learning process that not only produces an output of students who can graduate from school but also produce students who have religious characters. This research uses a qualitative approach with the type of case study method. The data collection techniques used were interviews, observation, and documentation. The results are the synergistic relationship and active role of all parties; in this case, the school and parents have successfully shaped the Islamic religious character. Students' character is built on a strong foundation from the family and strengthened through the Islamic education system in schools.